Análisis del uso docente de las categorías del conocimiento del modelo TPACK del área de matemáticas en la Unidad Educativa Fiscomisional Mons. Luis Alfonso Crespo Chiriboga durante el primer trimestre del año lectivo 2024-2025 - Romero Gonzaga, Ronald Michael (2025)
The purpose of this study was to analyze the use of the knowledge categories of the TPACK model (Technological Pedagogical Content Knowledge), translated into Spanish as Technological, Pedagogical and Disciplinary Knowledge, which was carried out in the area of mathematics in Msgr. Luis Alfonso Crespo Chiriboga Fiscomisional Educational Unit, during the first quarter of the 2024-2025 school year, since this model integrates technological, pedagogical and content knowledge, which are essential elements to enhance the teaching-learning processes through digital technologies; the methodology used was framed in a deductive method, quantitative approach, descriptive scope and a cross-sectional design; In addition, a structured questionnaire was adapted and subsequently applied to a sample of 10 teachers in the area of mathematics, out of the total of 44 teachers in the institution, using the survey technique; the instrument, based on the Likert scale, helped the diagnosis of three dimensions of the TPACK model: technological, pedagogical and content knowledge. In the results it was possible to identify three types of categories: technological, pedagogical and content; on the other hand, in the use it was evidenced that pedagogical and content knowledge have a majority percentage and according to the Likert scale in “always”, while the technological one in “occasionally”, which allows concluding that teachers dominate the pedagogical and disciplinary dimension, but show limitations in the technological one. It is recommended that the directors of the institution implement continuous training in the use of educational technologies to optimize the teaching-learning process